Influences on Indigenous and Pacific students' health career choices: a longitudinal cohort study. Issue 2 (4th May 2019) - Crawford, Ruth; Turvey, Janet
Abstract : Background : It is not understood how Māori and Pacific students in New Zealand choose nursing as a health career. Findings regarding influences arose from a study focusing on an incubator programme in New Zealand. Objectives : The aim of this study was to investigate whether secondary school students' participation in an Incubator Programme at secondary school influences students' choice of tertiary education. One of the aims of Programme Incubator (PI) is to encourage Indigenous (Māori) and Pacific students to consider a career in health. Methods : This longitudinal cohort study followed two cohorts of secondary school students from five schools. Participants completed a survey before and after participating in PI. Results : Of possible career options, nursing was the most common. Influences on career choices were personal experience, exposure to the media, careers advisors and teachers. Conclusions : PI is more attractive to Māori and Pacific people, than other populations. PI has been found to broaden and confirm available career options for some students. Nursing is a popular career choice for secondary students.